Implications of SARSr-CoV 2 infection in thalassemias: Do patients fall into the “high clinical risk” category? - Karimi, Mehran; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
We’re all flying blind regarding coronavirus, but it’s fair to think if thalassemic patients are particularly vulnerable to SARS-COV-2 infection or are at potential higher risk of complications from COVID-19 than normal population, specially when they become older. The frustrating thing is that, right now, this virus is still new. It only came to the attention of the World Health Organization at the end of December. Very few cases in thalassemia have so far been reported; is this due to lack of testing or a true lack of infection/susceptibility? However, we believe that more data should be collected to better characterise the impact of SARS-CoV-2 infection in patients with thalassemias. Therefore, a multicenter registry and the collection of comprehensive data from both positive COVID-19 thalassemia major and non-transfusion dependent thalassemia are necessary to clarify debated issues. In the meantime an early and vigilant monitoring along with high quality supportive care are needed in thalassemic patients at high risk for SARS-CoV-2 infection.